CREATION OF SENSORY PROFILES OF RIESLING WINES FROM EUROPE, AMERICA AND OCEANIA AND THEIR COMPARATIVE CHARACTERISTICS - VERECHUK, Olena; KAMENEVA, Natali (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Effective work at the winery is possible only if the final result is taken into account. Riesling wines have a different organoleptic profile depending on the country of cultivation, zone, climate and weather conditions. High temperatures affect the high concentration of TDN in the berry, more moderate forms herbal, fruit and mineral descriptors. Of course, work at the winery is also important. This work presents the results of the research of seven Riesling wines from different countries of the world: France, Italy, Germany, Austria, Ukraine, New Zealand and Australia. All wines are from the same harvest year and are made using similar technology. Looking at the possible difference in grape clones, terroir and yeast, the author understands the discrepancy in descriptors, but the main criteria for wine quality are objective indicators. The most important indicators of the quality of wines are balance and aftertaste, the whole range of descriptors and indicators of taste, in the end, should answer two questions - how good is the balance and long aftertaste. The higher the score, the higher the quality of the product. The analysis carried out by the author shows that the Riesling wines produced in New Zealand, Austria and Germany received the highest indicators of balance and aftertaste. These same samples received the highest points according to the scoring method, in addition, the first two have the highest ratings in the categories "aroma intensity" and "taste intensity". Another important criterion of wines from the Riesling variety - minerality - is also the largest in the above three wines. The Ukrainian sample turned out to have good descriptors of berry, floral and stone aromas, and has good acidity. These data may indicate the peculiarity of the Ukrainian terroir, but still require additional research. The obtained data can be used to improve the organoleptic profile of Riesling wines grown in Ukraine.
Keywords: wine; Riesling; descriptor; sensory profile; balance; aftertaste